2018
DOI: 10.2196/11373
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Patient-Reported Outcomes Using the International Consortium for Health Outcome Measurement Dataset in a Major German University Hospital: Observational Study

Abstract: BackgroundCollecting patient-reported outcome (PRO) data systematically enables objective evaluation of treatment and its related outcomes. Using disease-specific questionnaires developed by the International Consortium for Health Outcome Measurement (ICHOM) allows for comparison between physicians, hospitals, and even different countries.ObjectiveThis pilot project aimed to establish a digital system to measure PROs for new patients with breast cancer who attended the Charité Breast Center This approach shoul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…During an assessment period of 1 year, we achieved an inclusion rate of 66.5% of patients with a diagnosed affective disorder. This rate is similar to those reported from other investigations performed on the general population and nonpsychiatric patient groups, which indicates that major depressive disorder or bipolar disorder symptomology does not constitute a barrier toward participation [37,38]. Adherence to assessments was high, and the dropout rate after initial participation was very low.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…During an assessment period of 1 year, we achieved an inclusion rate of 66.5% of patients with a diagnosed affective disorder. This rate is similar to those reported from other investigations performed on the general population and nonpsychiatric patient groups, which indicates that major depressive disorder or bipolar disorder symptomology does not constitute a barrier toward participation [37,38]. Adherence to assessments was high, and the dropout rate after initial participation was very low.…”
Section: Discussionsupporting
confidence: 88%
“…However, the percentage of participants who needed assistance was comparatively small, and even those who did require assistance were able to complete assessments regularly, which suggests that their difficulties with handling the equipment did not stop them from participating. Although our study did not assess subjective attitudes toward technology, previous studies [38,46] found that digital methods of data collection are well-accepted even among older adults. It can also be expected that technological literacy will rise in older populations over the years, as smartphones and tablets are becoming increasingly ubiquitous, which will alleviate the difficulties for this specific age group in the future.…”
Section: Discussionmentioning
confidence: 92%
“…During the assessment period of one year, we achieved an inclusion rate of 66.5% of patients with a diagnosed affective disorder. This rate is similar to that reported from other investigations performed on the general population and non-psychiatric patient groups, which indicates that MDD symptomology does not constitute a barrier towards participation (Grobbee et al, 2005; Karsten et al, 2018). Exclusion by the clinician or researcher and refusal to participate by the patients themselves were largely not due to symptom severity or cognitive impairment but for organisational reasons or a general disinterest in the study, which mirrors reasons for non-participation in research from non-psychiatric populations (Brintnall-Karabelas et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…However, the percentage of participants who needed assistance was comparatively small and even those who did require assistance were able to complete assessments regularly, which suggests that their difficulties with handling the equipment did not stop them from participating. Although our study did not assess subjective attitudes toward technology, previous studies found that digital methods of data collection are well-accepted even among older adults (Horevoorts, Vissers, Mols, Melissa, & Van De Poll-Franse, 2015; Karsten et al, 2018). It can also be expected that technological literacy will rise in older populations over the years, as smartphones and tablets are becoming increasingly ubiquitous, which will alleviate the difficulties for this specific age group in the future.…”
Section: Discussionmentioning
confidence: 98%
“…The standard sets should be applied in both routine clinical practice and clinical studies in order to standardize the measured outcomes worldwide [ 36 ], enabling global comparisons and benchmarking and driving improvements in relevant patient outcomes [ 35 , 37 ]. Currently, several healthcare institutions have adopted ICHOM standards for different conditions, such as pregnancy and childbirth [ 38 ], breast cancer [ 39 ], hip and knee osteoarthritis [ 25 ]. Although efforts in this regard have increased, there is still a limited understanding of how these standard sets perform in clinical settings, as few implementations are described in the literature.…”
Section: Discussionmentioning
confidence: 99%